Niewydolność serca i płuc, transplantologiaInterventional bronchoscopy procedures in lung transplant recipients including own experiences - Wojarski, Jacek; Żegleń, Sławomir; Kucewicz-Czech, Ewa; Przybylski, Roman; Głowacki, Jan; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
The paper presents a brief description of interventional bronchoscopy procedures in lung transplant recipients associated with bronchomalacia, anastomosis stenoses, or endobronchial benign stenoses connected with fungal or bacterial infections. Described procedures were successfully performed in the Silesian Centre for Heart Diseases in Zabrze. Their effectiveness and complications are briefly discussed.